The Role of Digital Technologies in Building Research Competencies of Future Doctors of Philosophy - Оliinyk, Iryna; Bidzilya, Yuriy; Solomin, Yevhen; Shapovalova, Halyna; Hetsko, Hanna (Journal of Education Culture and Society, 2023)
Aim. Digital technologies support learning, so the search for innovative approaches is ongoing. The aim of the research is to study the role of digital technologies in developing research competencies of future Doctors of Philosophy (PhDs). The aim was achieved through the Likert scale, calculation of the variability coefficients, the level of acquired knowledge and Cohen’s kappa coefficient, correlation index.Methods. Continuous study of the methodological foundations of scientific research was provided through the iSpring Market, and Comindwork online programmes. Learning English involved using the BBC Learning English application, while OpenLearning was used to develop knowledge on the dissertation topic.Results. It was determined that the respondents who studied pedagogy, psychology, social work (Group 1) expanded their basic knowledge the most (21%). Respondents who studied journalism (Group 2) developed autonomous learning (23%). The future PhDs acquired knowledge in three subjects at a high level, contributing to developing professional competencies.Conclusions. The practical significance of the research is in developing training for PhDs with the use of digital technologies. The research prospects are related to comparing the effectiveness of training of first- and second-year PhDs as a result of the use of innovative technologies.Key words: information technologies, scientific research, research process, critical thinking, technical competence